Isolation and Determination of Cumarin Constituent "Aurapten" from Ferula persica var. latisecta an Endemic Medicinal Plant of Iran - S Sarvi; M Taherkhani; M Ghorbani Nohooji (Institue of Medicinal Plants, ACECR, 2018)
Background: Medicinal plants of Genus Ferula are prennial herbs of Apiaceae family which are widely distributed all around the word. Many of Feula species are exclusive and endemic to Iran which has widespread uses in traditional medicine as food additive, as well as a carminative, antispasmodic and expectorants. Coumarins, flavonoids and sulfur-containing compounds with different biological effects have been reported from the plant. Objective: The phytochemical investigation on total extract of the aerial parts of Ferula persica Willd var. Latisecta collected from the Central Alborz Protected Area was subjected with the aim of purification and determination of main metabolite constituents of the plant extract. Methods: Dried and powdered plant material was extracted by maceration method. Then the extract was concentrated under reduced pressure to leave a residue which was defatted and chromatographed on a silica gel column by increasing slightly the polarity with solvent. After the serial fractionation the fractions were compared by TLC, and those giving similar coumarin spots were combined and further purified on PLC to give a pure natural compound. Results: After the purification step the remarkable constituents were obtained. Elucidation of results by spectral methods (IR, 1H-NMR, 13C-NMR and DEPT) demonstrate that a coumarin namely: Auraptene (7-genaryloxycoumarin) was isolated from the aerial parts of F. persica. var. latisecta. Conclusion: F. persica is an endemic and endangered species of medicinal plants of Iran which contains different natural compounds such as coumarins. So the Protection of the plant for its economic and scientific uses is so important.